Full-time faculty and civil service salaries at Illinois colleges and universities - Illinois. Board of Higher Education ([Springfield, Ill. : The Board, 1998)
Compares average salaries for fiscal years 1985, 1990, and 1996-1998 for Illinois public and independent colleges and universities and the Illinois Mathematics and Science Academy with select economic indicators and with salaries at comparable institutions.
"September 1, 1998."
Caption title.
Mode of access: Internet.
Keywords: Universities and colleges -- Employees -- Salaries, etc. -- Illinois; Universities and colleges -- Faculty -- Salaries, etc. -- Illinois